2011
DOI: 10.1371/journal.pone.0019124
|View full text |Cite
|
Sign up to set email alerts
|

The Telomere Binding Protein TRF2 Induces Chromatin Compaction

Abstract: Mammalian telomeres are specialized chromatin structures that require the telomere binding protein, TRF2, for maintaining chromosome stability. In addition to its ability to modulate DNA repair activities, TRF2 also has direct effects on DNA structure and topology. Given that mammalian telomeric chromatin includes nucleosomes, we investigated the effect of this protein on chromatin structure. TRF2 bound to reconstituted telomeric nucleosomal fibers through both its basic N-terminus and its C-terminal DNA bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 76 publications
1
30
0
Order By: Relevance
“…When nucleosome arrays were assembled on telomeric repeats in the presence of TRF2 in vitro, the distance between nucleosomes increased and became less regular (52). In vitro analytical agarose gel electrophoresis and AFM studies revealed that TRF2, as well as the TRF2 DNA binding domain, promotes the folding of nucleosomal arrays into more compact structures (53,54), thus generating results that seem to be inconsistent with the in vivo studies mentioned earlier.…”
Section: Telomere Repeat Direct Binders Trf1 and Trf2mentioning
confidence: 78%
See 1 more Smart Citation
“…When nucleosome arrays were assembled on telomeric repeats in the presence of TRF2 in vitro, the distance between nucleosomes increased and became less regular (52). In vitro analytical agarose gel electrophoresis and AFM studies revealed that TRF2, as well as the TRF2 DNA binding domain, promotes the folding of nucleosomal arrays into more compact structures (53,54), thus generating results that seem to be inconsistent with the in vivo studies mentioned earlier.…”
Section: Telomere Repeat Direct Binders Trf1 and Trf2mentioning
confidence: 78%
“…The effects of TRF2 on nucleosome organization have also been extensively studied in vivo (50)(51)(52) and in vitro (52)(53)(54). A recent chromatin immunoprecipitation and MNase mapping assay demonstrated that TRF2 overexpression reduces the nucleosome density and increases the internucleosomal distance at telomeres in vivo (52).…”
Section: Telomere Repeat Direct Binders Trf1 and Trf2mentioning
confidence: 99%
“…TRF2 and TRF1 both consist of four domains: a C-terminal MYB domain required for binding to telomeres, a flexible hinge domain involved in protein–protein interactions, a TRFH domain required for homodimerization 40 and chromatin compaction 41,42 , and a divergent amino (N)-terminal region rich in basic amino acids in TRF2 and acidic residues in TRF1. To identify the molecular properties of TRF2 involved in regulating TERRA transcription, we swapped, inspired by a previous study 41 , several domains between TRF2 and TRF1 (refs 43,44) in cDNA constructs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the molecular properties of TRF2 involved in regulating TERRA transcription, we swapped, inspired by a previous study 41 , several domains between TRF2 and TRF1 (refs 43,44) in cDNA constructs (Fig. 5a) and expressed them in HeLa cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation